2017
DOI: 10.21451/1984-3143-ar895
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-art of boar sperm preservation in liquid and frozen state

Abstract: Pig breeding is mainly conducted through Artificial Insemination (AI) in Western and developing countries. Apart from requiring specific catheters and trained staff, preserving boar semen in proper conditions is needed to ensure high reproductive performances. Although, at present, boar sperm may be preserved in liquid (15-17ºC) or frozen states, more than 95% of AIs are conducted using liquid semen. The present work reviews the state-the-art of these two preservation technologies. Thus, the composition and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 129 publications
3
68
0
4
Order By: Relevance
“…A boar semen sample can become contaminated as a result of the infection of the male reproductive tract or during the collection and processing of the semen to obtain seminal doses (Bryła & Trzcińska, ; Kuster & Althouse, ); factors like glucose and storage temperature at 15–18°C also promote bacterial proliferation (Yeste, ). Maroto Martín et al () determined that 75% of the analysed samples were contaminated with at least one type of bacterium, with Escherichia coli being the most common; another study showed that Chlamydia suis remains viable and infectious, being capable of spermicidal activity after 7 days of storage at 17°C (Hamonic, Pasternak, Käser, Meurens, & Wilson, ).…”
Section: Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…A boar semen sample can become contaminated as a result of the infection of the male reproductive tract or during the collection and processing of the semen to obtain seminal doses (Bryła & Trzcińska, ; Kuster & Althouse, ); factors like glucose and storage temperature at 15–18°C also promote bacterial proliferation (Yeste, ). Maroto Martín et al () determined that 75% of the analysed samples were contaminated with at least one type of bacterium, with Escherichia coli being the most common; another study showed that Chlamydia suis remains viable and infectious, being capable of spermicidal activity after 7 days of storage at 17°C (Hamonic, Pasternak, Käser, Meurens, & Wilson, ).…”
Section: Antibioticsmentioning
confidence: 99%
“…Adequate temperature management during semen processing is central to the quality of the stored samples, since mammalian sperm, especially boar sperm, are sensitive to a rapid reduction in temperature due to the physicochemical characteristics of the membranes (Parks & Lynch, ), altering the lipid phase transition and the phase separation processes (Schulze, Henning, Rüdiger, Wallner, & Waberski, ), which occur at 18–24°C (Canvin & Buhr, ), reducing the lateral movements of the membrane phospholipids and causing irreversible changes in the membrane proteins (Canvin & Buhr, ; Yeste, ). There is a greater membrane protein/phospholipid ratio (1.26) and a smaller proportion of cholesterol (0.26) in boar sperm that lowers the tolerance to the effect on the temperature changes compared to other species like human and bull (Parks & Lynch, ).…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In swine production, artificial insemination (AI) is used with liquid-stored semen. Extenders are used to increase the volume of the ejaculate, provide energy to sperm, protect against cold shock, maintain a stable pH, ensure an adequate osmotic pressure, and prevent bacterial growth during storage (Yeste, 2017). The extenders are divided into two main groups according to the capability of promoting the viability of sperm cells over time: short-term (up to three days) and long-term (more than four days) (Yeste, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Cryo-induced damage to spermatozoa is attributed to membrane deterioration caused mainly by the formation of intracellular ice and increased oxidative stress, resulting in a loss of the sperm fertilizing ability. 3 It is noteworthy that ageing-dependent processes in frozen-thawed semen occur in different sperm compartments, and are associated with membrane modifications of specific lipid-protein interactions, activation of an apoptosis-like mechanism and reduced genomic integrity, which consequently compromise sperm cryo-survival.…”
mentioning
confidence: 99%